2021
DOI: 10.1177/13623613211051480
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the impact of the first and second wave of COVID-19 lockdown on Slovak families with typically developing children and children with autism spectrum disorder

Abstract: The aim of this research was to compare the mental health of families with children diagnosed with autism spectrum disorder or typically developing children, during the first and the second wave of COVID-19 outbreak in Slovakia. The study is mainly focused on the prevalence of depression, anxiety, and stress among the parents and maladaptive behavior or sleep disturbances of their children. Our research sample consisted of 332 caregivers, 155 of which have children with autism spectrum disorder; 179 surveyed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 35 publications
3
30
1
3
Order By: Relevance
“…From a mental health perspective, depression is a huge burden on health ( 11 ). In Slovakia, together with the COVID-19 pandemic, depressive symptoms also appeared across the population ( 12 , 13 ), while depression is considered not only a health but also an economic burden in this country ( 14 ). In addition, it has been proven that Slovak family members of patients in intensive care units report a higher prevalence of depression ( 15 ), which can also be expected in COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%
“…From a mental health perspective, depression is a huge burden on health ( 11 ). In Slovakia, together with the COVID-19 pandemic, depressive symptoms also appeared across the population ( 12 , 13 ), while depression is considered not only a health but also an economic burden in this country ( 14 ). In addition, it has been proven that Slovak family members of patients in intensive care units report a higher prevalence of depression ( 15 ), which can also be expected in COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%
“…The domain behavior was addressed in 22 articles, all of which described changes in behavior (Amorim et al, 2020 ; Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Jacques et al, 2022 ; Kawabe et al, 2020 ; Lugo-Marín et al, 2021 ; Mete Yesil et al, 2022 ; Morris et al, 2021 ; Mumbardó-Adam et al, 2021 ; Mutluer et al, 2020 ; Nuñez et al, 2021 ; Panjwani et al, 2021 ; Polónyiová et al, 2022 ; Rabbani et al, 2021 ; Sergi et al, 2021 ; Tokatly Latzer et al, 2021 ; Türkoğlu et al, 2020 , 2021 ; Vasa et al, 2021 ). Medium level of evidence was observed in eight papers (Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; Türkoğlu et al, 2021 ; Vasa et al, 2021 ) and the hypothesis of worsening behavior was confirmed by six articles, Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; and Türkoğlu et al, 2021 .…”
Section: Resultsmentioning
confidence: 99%
“…Medium level of evidence was observed in eight papers (Berard et al, 2021 ; Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; Türkoğlu et al, 2021 ; Vasa et al, 2021 ) and the hypothesis of worsening behavior was confirmed by six articles, Bhat, 2021 ; Colizzi et al, 2020 ; Corbett et al, 2021 ; Hosokawa et al, 2021 ; Nuñez et al, 2021 ; and Türkoğlu et al, 2021 . Most articles (n = 13) observed an resurgence of previous behavioral problems (Berard et al, 2021 ; Bhat, 2021 ; Hosokawa et al, 2021 ; Mete Yesil et al, 2022 ; Mutluer et al, 2020 ; Nuñez et al, 2021 ; Panjwani et al, 2021 ; Polónyiová et al, 2022 ; Sergi et al, 2021 ; Tokatly Latzer et al, 2021 ; Türkoğlu et al, 2020 , 2021 ; Vasa et al, 2021 ), while others (n = 5) observed the emergence of new behavioral issues (Corbett et al, 2021 ; Mete Yesil et al, 2022 ; Mumbardó-Adam et al, 2021 ; Mutluer et al, 2020 ; Vasa et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations